Caracterização de leguminosas para adubação verde de canaviais em solo de Tabuleiro Costeiro, Penedo, Alagoas - Cerqueira, Danilo César Oliveira de (2011)
The expansion of area cultivated with sugar cane incorporates every season, areas of poor soils, low fertility and low CEC. Green manure can be used in the renovation of the reeds with great benefits to soil, however, climate and soil for each condition it is important for a study to define the most suitable legumes to serve as green manure and to evaluate the effects of culture cane sugar. This experimental study aimed to characterize growth and nutrient uptake of certain species of legumes used as green manure and their influences on productivity and technological indices of cane sugar in the soil of the Coast Plains, Penedo, Alagoas. This experiment was conducted in the area of commercial exploitation, in Perocabinha Farm, Lot 25, Paisa Power Plant, located in the city of Penedo, Alagoas. The average temperature characteristic of the region is 25.8 ° C with maximum temperatures of 30.2 ° C and mean minimum of 21.3 ° C. The average annual precipitation is 1,700 mm and the rainy season extends from April to early September. The experimental area was located in a Coastal Board Hapludalf. This work was organized to run in two steps. In the first phase was carried out planting in the experimental arrangement of some legume species, phase implemented in the rainy season, the treatments were: T1= Crotalaria spectabilis T2= Crotalaria juncea, T3= Crotalaria ochroleuca, T4= Crotalaria breviflora, T5= pigeonpea, T6= Filter cake, T7 = Witness. In the final phase, in succession to green manure, were the renovation of the cane field with just one variety of cane sugar, RB98579, which was planted on the same plots with the aim of evaluating the influence of green manure on productivity culture. The experiment consisted of seven treatments, five replicates and their plots had 70 square meters (7m x 10m). The statistical design was randomized blocks and the results were subjected to analysis of variance. After 100 days of cultivation, all assessments were carried out in pulses and cane sugar measurements were made at the end of the cycle. There are several differences that occur between legumes studied, biomass production, nutrient accumulation and nutrient efficiency also differed by a green manure to another. It was found that a gain of 15 t ha- 1 of cane sugar when sugar cane is grown in rotation green manures. The industrial output is increased by 6 t ha-1 sugar when using the green manure in cane fields.